EVALUATION OF THE RESULTS OF RADIOLOGICAL DIAGNOSIS OF TRAUMATIC RETROPERI-TONEAL HEMORRHAGE AND RENAL DAMAGE - Гасимзаде, Г.Ш. (World of Medicine and Biology, 2017)
We examined 94 patients with retroperitoneal bleeding and kidney damage with closed abdominal trauma, the mean age of 33.22 ± 3.44 years. In 47.9% of the injured, the cause of the damage was an accident, 27.7% - a fall from the height, 14.9% - a stomach and waist and 9.6% in a sports jump. The sufferers made ultrasound and spiral CT. Immediately upon entering the presence of free fluid were detected in 87.2 per cent, on the next day - at 9.6% and after another day - 3.2% of sufferers. In 68.1% of cases was determined by the type of impregnation, at 31.9% - type of clots. With ultrasound the fuzzy contours detected in 100% of cases, the heterogeneity of the wheat plant's structure - at 83.3%, the increase in size at 61.1%, subcapsular changes of the parenchyma - in 16.7% of cases. More accurate and extensive information obtained with spiral CT. In patients with suspected HCC and kidney injury ultrasound should be performed immediately upon admission and again within 1-2 days. Spiral CT allows more accurate and clear picture of retroperitoneal bleeding, determine the severity of kidney injury and the condition of the structure of the parenchyma.
Keywords: retroperitoneal bleeding; injury to kidney; ultrasound; spiral CT scan; free fluid; sonogram